Large-scale Tikhonov regularization via reduction by orthogonal projection - Lampe, Jörg; Reichel, Lothar; Voss, Heinrich (Linear algebra and its applications, 2012)
This paper presents a new approach to computing an approximate solution of Tikhonov-regularized large-scale ill-posed least-squares problems with a general regularization matrix. The iterative method applies a sequence of projections onto generalized Krylov subspaces. A suitable value of the regularization parameter is determined by the discrepancy principle.